Ectopic insert-dependent neuronal expression of GFAP promoter-driven AAV constructs in adult mouse retina - Le, Nguyet; Appel, Haley; Pannullo, Nicole; Hoang, Thanh; Blackshaw, Seth (Frontiers in Cell and Developmental Biology, 2022)
Direct reprogramming of retinal Müller glia is a promising avenue for replacing photoreceptors and retinal ganglion cells lost to retinal dystrophies. However, questions have recently been raised about the accuracy of studies claiming efficient glia-to-neuron reprogramming in retina that were conducted using GFAP mini promoter-driven adeno-associated virus (AAV) vectors. In this study, we have addressed these questions using GFAP mini promoter-driven AAV constructs to simultaneously overexpress the mCherry reporter and candidate transcription factors predicted to induce glia-to-neuron conversion, in combination with prospective genetic labeling of retinal Müller glia using inducible Cre-dependent GFP reporters. We find that, while control GFAP-mCherry constructs express faithfully in Müller glia, 5 out of 7 transcription factor overexpression constructs tested are predominantly expressed in amacrine and retinal ganglion cells. These findings demonstrate strong insert-dependent effects on AAV-based GFAP mini promoter specificity that preclude its use in inferring cell lineage relationships when studying glia-to-neuron conversion in retina.